USP39 interacts with SIRT7 to promote cervical squamous cell carcinoma by modulating autophagy and oxidative stress via FOXM1 - Juanpeng Yu; Shuai Yuan; Jinglin Song; Shengsheng Yu (Journal of Translational Medicine, 2023)
Abstract Background Sirtuin 7 (SIRT7) is an oncogene that promotes tumor progression in various malignancies, however, its role and regulatory mechanism in cervical squamous cell carcinoma (CSCC) is unknown. Herein, we attempted to investigate the functional role and molecular mechanism of SIRT7 underlying CSCC progression. Methods SIRT7 expression was evaluated in CSCC cells using various assays. We then used a series of function gain-and-loss experiments to determine the role of SIRT7 in CSCC progression. Furthermore, mechanism experiments were conducted to assess the interaction between SIRT7/USP39/FOXM1 in CSCC cells. Additionally, rescue assays were conducted to explore the regulatory function of USP39/FOXM1 in CSCC cellular processes. Results SIRT7 was highly expressed in CSCC patient tissues and cell lines. SIRT7 deficiency showed significant repression on the proliferation, and autophagy of CSCC cells in vitro and tumorigenesis in vivo. Similarly, apoptosis and ROS production in CSCC cells were accelerated after the SIRT7 knockdown. Moreover, SIRT7 and USP39 were found colocalized in the cell nucleus. Interestingly, SIRT7 was revealed to deacetylate USP39 to promote its protein stability in CSCC cells. USP39 protein was also verified to be upregulated in CSCC tissues and cells. USP39 silencing showed suppressive effects on CSCC cell growth. Mechanistically, USP39 was revealed to upregulate SIRT7 by promoting the transcriptional activity of FOXM1. Rescue assays also indicated that SIRT7 promoted autophagy and inhibited ROS production in CSCC cells by regulating USP39/FOXM1. Conclusion The SIRT7/USP39/FOXM1 positive feedback network regulates autophagy and oxidative stress in CSCC, thus providing a new direction for CSCC-targeted therapy. Graphical Abstract